2017
DOI: 10.3389/fnut.2017.00052
|View full text |Cite
|
Sign up to set email alerts
|

Managing Rheumatoid Arthritis with Dietary Interventions

Abstract: Self-help by means of dietary interventions can help in management of various disorders including rheumatoid arthritis (RA), a debilitating autoimmune disease. Dietary interventions necessitate a widespread appeal for both patients as well as clinicians due to factors including affordability, accessibility, and presence of scientific evidences that demonstrate substantial benefits in reducing disease symptoms such as pain, joint stiffness, swelling, tenderness and associated disability with disease progression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(96 citation statements)
references
References 180 publications
(166 reference statements)
0
85
0
1
Order By: Relevance
“…Approximately 1% of the world population suffers from this disease, and it puts a tremendous economic burden on the society. 2 The management of RA is limited to retarding the progression of the disease, improving functional capacity, and relieving pain. Besides, over time, patients with severe cases have to receive surgical interventions, such as total hip arthroplasty.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 1% of the world population suffers from this disease, and it puts a tremendous economic burden on the society. 2 The management of RA is limited to retarding the progression of the disease, improving functional capacity, and relieving pain. Besides, over time, patients with severe cases have to receive surgical interventions, such as total hip arthroplasty.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the growing evidence of the relationship between diet and RA symptoms, research in the field is still limited to mostly observational studies; however, there are quite a few interventional studies in which diet has been evaluated as a strategy to improve RA symptoms. A detailed review of the studies can be found here [206][207][208]. Most interventions combine a diet with high intake of vegetables, fruit, and antioxidants with periods of fasting.…”
Section: Studies Of Beneficial Effect Of Diet In Ramentioning
confidence: 99%
“…Another nutritional intervention which is associated with an improved clinical outcome is the Mediterranean diet [141]. Among Mediterranean diets, the Cretan diet has been proposed to be especially beneficial, perhaps due to the high intake of fresh vegetables, fruit, legumes and cereals [142].…”
Section: General Interventions and The Gutmentioning
confidence: 99%
“…A meta-analysis focusing on the effect of the Mediterranean diet intervention on inflammation and endothelial function found that adherence reduced inflammatory markers CRP, IL-6 and intercellular adhesion molecule 1 (ICAM-1) [145]. As the Mediterranean diet has been shown to have beneficial effects for RA and is rich in n-3 fatty acids, phytochemicals, unrefined carbohydrate and oleic acid, other studies have also focused on the effects of single nutrients on RA, which is reviewed in detail elsewhere [141].…”
Section: General Interventions and The Gutmentioning
confidence: 99%